Selective survival of calretinin and vasoactive-intestinalpeptide- containing nerve elements in human chagasic submucosa and mucosa - Jabari, Samir; Da Silveira, Alexandre B.M.; De Oliveira, Enio; Neto, Salustiano D.; Quint, Karl; Neuhuber, Winfried; Brehmer, Axel (Cell and Tissue Research, 2012)
Chronic Chagas' disease is frequently characterized by massive myenteric neuron loss resulting in megacolon with severely and irreversibly disturbed motility. Here, we focused on two submucosal neuron populations, immunoreactive for calretinin (CALR) or somatostatin (SOM), and their respective mucosal nerve fibres in chagasic megacolon. Surgically removed megacolonic segments of seven chagasic patients were compared with seven ageand region-matched non-chagasic control segments. Evaluation included immunohistochemical triple-staining of cryosections for CALR, SOM and peripherin or for CALR and vasoactive intestinal peptide (VIP) and of submucosal whole-mounts for CALR, SOMand the pan-neuronal marker anti-HuC/D. Submucosal neuron counts in chagasic tissue revealed neuron numbers reduced to 51.2 % of control values. In cryosections, nerve fibre area measurements revealed 8.6 % nerve fibre per mucosal area in control segments, but this value decreased to 1.5 % in megacolonic segments. In both evaluations, a disproportionate decrease of SOM-reactive nerve elements was observed. The proportions of SOM-positive neurons related to the total neuron number declined to 2 % (control 10 %) and the proportion of SOM-reactive mucosal nerve fibres related to the whole mucosal area to 0.014 % (control 1.8 %)in chagasic tissue. The second set of cryosections revealed extensive colocalization of CALR with VIP in both surviving submucosal perikarya and mucosal nerve fibres. We suggest that VIP, a neuroprotective and neuroeffectory peptide typically contained in submucosal neurons, allows both the VIP-containing neurons to endure and the patients to survive by maintaining their mucosal barrier, despite the almost complete loss of colonic motility for decades. © Springer-Verlag 2012.
Keywords: Chagasic megacolon; Enteric nervous system; Human; Mucosa; Submucosal plexus; Vasoactive intestinal peptide